Exploiting crosslinked decellularized matrix to achieve uterus regeneration and construction - Qing Yao (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Decellularized extracellular matrix (dECM) has been considered as a promising scaffold in xenotransplantation, yet natural tissue dECM is often mechanically weak and rapidly degraded, compromising the outcomes. How to restore the mechanical strength and optimise the in vivo degradation, but maintain the microstructure and maximumly suppress the immune rejection, remains challenging. For this aim, we prepared and characterised various crosslinked decellularized rabbit uterus matrix (dUECM) and evaluated in vivo performance after uterus xenotransplantation from rabbit to rat. Naturally derived genipin (GP) and procyanidins (PC) were chosen to crosslink the dUECM, producing significant mechanical enhanced crosslinked-dUECM along with prolonged enzymatic degradation rate. Xenogeneic subcutaneous graft studies revealed that PC- and GP-crosslinked dUECM experienced significant cell infiltration and caused low immune reactions, indicating the desired biocompatibility. In vivo transplantation of GP- and PC-crosslinked dUECM to a uterus circular excised rat yielded excellent recellularization ability and promoted uterus regeneration after 90 days. While the reconstruction efficacy of crosslinked dUECM is highly depended on the crosslinking degree, crosslinking condition must be carefully evaluated to balance the role of crosslinked dECM in mechanical and biological support for tissue regeneration promotion.